Theatre's Heterotopias - Tompkins, J. author. aut Link
XI, 231 p.
Keywords: Theatre's Heterotopias analyses performance space, using the concept of heterotopia: a location that, when apparent in performance, refers to the actual world, thus activating performance in its culture. Case studies cover site-specific and multimedia performance, and selected productions from the National Theatre of Scotland and the Globe Theatre.